A “Fazenda do Zoo” de São Paulo como instrumento de Educação Ambiental. Araçoiaba da Serra, SP - Petri, Tiago (Universidade Federal de São Carlos, 2017)
This paper has as main objective to describe and analyze the Environmental Education Program of the São Paulo Zoo Farm as for its effectiveness and applicability as to Environmental Education and its principles. Having as tool of verification the related public and identifying the potential of the program as for the evaluation of the participants and their testimonials. This Program of Environmental Education aims the formation of teachers for the implementation of environmental projects in schools and guided field trips to the zoo’s farm, which is among the cities of Sorocaba, Araçoiaba da Serra and Salto de Pirapora, from countryside São Paulo state in Brazil. The farm produces 80% of all the food provided to the São Paulo Zoo’s animals, being so able to host many different cities in a Program of Environmental Education. The work had by method the documentary institutional analysis of reports and questionnaires applied by the researcher to teachers, students and monitors in the year 2015.
The "Farm of Sao Paulo's Zoo" as a tool of Environmental Education. Araçoiaba da Serra, Sao Paulo, Brazil
Keywords: Educação Ambiental; Zoológico de São Paulo; Fazenda do Zoo; Environmental Education; São Paulo Zoo; Zoo Farm; CIENCIAS HUMANAS::EDUCACAO